An Accelerated repair method for steel girders with severe end corrosion damage. (15th January 2022) - McMullen, Kevin F.; Zaghi, Arash E.
Graphical abstract: Highlights: Experimental investigation of an accelerated UHPC repair method for steel girder ends. Dowel rods were an alternative shear connector for headed studs to transfer loads. Unconventional formwork was evaluated to facilitate the construction process. Abstract: A novel repair method for corroded steel girder ends using ultra-high performance concrete (UHPC) has gained the attention of several departments of transportation. The method involves welding shear studs to the intact part of the web plate and encasing the end region in UHPC. This paper presents the findings of an experimental study on a full-scale girder aimed to assess the feasibility of rapid implementation of the repair. Reducing the construction complexities and time is critical in cases where access to the bridge is constrained or closing the bridge to traffic is not possible. To expedite and simplify repair construction, welded shear studs originally used to transfer loads to the UHPC cast were replaced with steel dowel rods. In place of conventional wooden formwork, a reusable flexible light-gauge sheet of steel was wrapped around the end. Installation of the shear connectors, installation of the form, and casting of the UHPC was completed by two workers within an eight-hour shift. The repaired girder was load tested after the UHPC gained a compressive strength of 96.5 MPa to demonstrate the adequacy of the repair for restoring the capacity of the intact girder end shortly after implementation. It is anticipated that this empirical data encourages the use of this repair technique to address the widespread problem of end corrosion in steel superstructures.